Rehabilitation and return-to-play following knee cartilage injuries-an international Delphi consensus statement - Samuel G. Lorentz; Eoghan T. Hurley; Richard M. Danilkowicz; Olufemi R. Ayeni; Jason L. Dragoo; Brian C. Lau; Mary K. Mulcahey; Joan C. Monllau; Clayton W. Nuelle; Scott A. Rodeo (Elsevier, 2024)
Introduction: Articular cartilage injuries of the knee are a complex and challenging clinical pathology. Objectives: The purpose of this study was to establish consensus statements via a Delphi process on rehabilitation and return to play (RTP) following knee cartilage injuries. Methods: A consensus process on knee cartilage injuries utilizing a modified Delphi technique was conducted. Seventy-nine surgeons across 17 countries participated in these consensus statements. Eleven questions were generated on rehabilitation and RTP, with 3 rounds of questionnaires and final voting occurring. Consensus was defined as achieving 80% to 89% agreement, whereas strong consensus was defined as 90% to 99% agreement, and unanimous consensus was defined as 100% agreement with a proposed statement. Results: Of the 11 total questions and consensus statements on rehabilitation and RTP developed from 3 rounds of voting, 0 achieved unanimous consensus, 2 achieved strong consensus, 4 achieved consensus, and 5 did not achieve consensus. Conclusions: The statements achieving consensus were related to the benefits of early motion and that concomitant procedures may alter the rehabilitation process. RTP following cartilage-related procedures typically follows a rehabilitation guideline largely dependent on the type of cartilage procedure. The statements that did not reach a consensus were related to specific timing to meet goals.